Behavior of Stress Components with State-Space Approach in Modified Couple Stress Thermoelastic Medium with Variable Conductivity - Krishan Kumar; Ravinder Kumar Sahrawat; Poonam (Research Updates in Mathematics and Computer Science Vol. 9, 2024)
The present investigation of a two-dimensional problem in “modified couple stress’s thermoelastic medium for a half-space is “established and state-space approach” followed by normal mode analysis has been applied to solve the problem. In control engineering, a state-space representation is a mathematical model of a physical system as a set of input, output and state variables related by first-order differential equations. In this chapter, a homogeneous isotropic modified couple stress thermoelastic half space for the Lord-Shulman [L-S] model and Green-Lindsay [G-L] model has been considered. The exact expressions for normal stress, tangential stress and couple stress are obtained. These quantities are calculated numerically and depicted graphically for a special model. A particular case of interest has also been deduced from the present investigation.